The Use of Minipigs for Preclinical Safety Assessment by the Pharmaceutical Industry: Results of an IQ DruSafe Minipig Survey. (April 2016) - Colleton, Curtis; Brewster, David; Chester, Anne; Clarke, David O.; Heining, Peter; Olaharski, Andrew; Graziano, Michael
The use of minipigs in preclinical safety testing of pharmaceuticals is considered an alternative to the more traditional dog and nonhuman primate (NHP) nonrodent species. Substantial evidence exists to suggest that the anatomy, physiology, and biochemistry of minipigs are similar enough to humans to consider them as valid nonrodent models for pharmaceutical safety testing. Since the utilization of minipigs was last assessed over 5 years ago, the Preclinical Safety Leadership Group (DruSafe) of the International Consortium for Innovation and Quality in Pharmaceutical Development conducted this survey to provide an updated assessment of the utility, perceived value, and impediments to the use of minipigs in preclinical safety testing. Of the 32 participating members of DruSafe, 15 responded to the survey representing both large and small companies. Respondents indicated that the minipig has been utilized mostly for short-term safety assessment studies with dermal, oral, and parenteral routes of administration. Minipigs are widely accepted as appropriate models for cardiovascular assessments and have been used to a limited extent for reproductive toxicology testing. Overall responses indicated that safety testing for large molecules using this species is relatively low due to a lack of background data, reagents or biomarkers, concerns regarding immune system characterization and poor suitability for developmental toxicity assessments. Most companies utilized contract research organizations for definitive safety toxicity assessment studies. Conclusions of this survey indicate that minipig is an acceptable nonrodent species largely limited to studies using small molecules, primarily dermal products, and results are comparable to those reported 5 years ago.